Homologous U-box E3 Ubiquitin Ligases OsPUB2 and OsPUB3 Are Involved in the Positive Regulation of Low Temperature Stress Response in Rice (Oryza sativa L.) - Byun, Mi Young; Cui, Li Hua; Oh, Tae Kyung; Jung, Ye-Jin; Lee, Andosung; Park, Ki Youl; Kang, Bin Goo; Kim, Woo Taek (Frontiers in Plant Science, 2017)
Rice U-box E3 Ub ligases (OsPUBs) are implicated in biotic stress responses. However, their cellular roles in response to abiotic stress are poorly understood. In this study, we performed functional analyses of two homologous OsPUB2 and OsPUB3 in response to cold stress (4°C). OsPUB2 was up-regulated by high salinity, drought, and cold, whereas OsPUB3 was constitutively expressed. A subcellular localization assay revealed that OsPUB2 and OsPUB3 were localized to the exocyst positive organelle (EXPO)-like punctate structures. OsPUB2 was also localized to the nuclei. OsPUB2 and OsPUB3 formed a hetero-dimeric complex as well as homo-dimers in yeast cells and in vitro. OsPUB2/OsPUB3 exhibited self-ubiquitination activities in vitro and were rapidly degraded in the cell-free extracts with apparent half-lives of 150 - 160 min. This rapid degradation of OsPUB2/OsPUB3 was delayed in the presence of the crude extracts of cold-treated seedlings (apparent half-lives of 200 - 280 min). Moreover, a hetero-dimeric form of OsPUB2/OsPUB3 was more stable than the homo-dimers. These results suggested that OsPUB2 and OsPUB3 function coordinately in response to cold stress. OsPUB2- and OsPUB3-overexpressing transgenic rice plants showed markedly better tolerance to cold stress than did the wild-type plants in terms of survival rates, chlorophyll content, ion leakage, and expression levels of cold stress-inducible marker genes. Taken together, these results suggested that the two homologous rice U-box E3 Ub ligases OsPUB2 and OsPUB3 are positive regulators of the response to cold stress.